Impacts of Information and Communication Technology on Tax Collection - Fatemeh Salari Kiskani (Shahid Bahonar University of Kerman, 2020)
Objective: According to recent financial and economic studies, taxes are the principal part of government revenues, and the stability of these revenues, compared to other volatile revenues, requires establishing an appropriate tax system. Although much works have been done in the last two decades to develop the Iranian tax system, there is still a long way before reaching a desirable tax system. It is noteworthy that the role of information and communication technologies, ICT, in the development of a tax system is remarkable. In the current situation, due to the increase in the number of enterprises and economic actors, the complexity of economic activities, and other intricacies, it is not possible to reform the government tax system, except through modernization of the system, use of ICT, and monitoring the financial and economic information of individuals, companies and electronic tax processes. The purpose of this study is to investigate the effects of ICT on corporate income tax collection from the perspective of tax officials and senior managers of companies and compare their views.  Method: The statistical population of this study consists of tax officials, senior managers, and accountants of companies across the country. Due to the uncertainty about population size, the sample size based on Cochran's formula with an error of 5% was obtained about 384 people. In this study, a quality questionnaire, whose reliability and validity have been verified, was used to collect data. Cronbach's alpha method was used for reliability testing. Also, in this study, to assess the content validity of the measurement tool, a preliminary questionnaire was presented as a "limited test" for some experts to provide recommendations for the questions. These recommendations were included in the final questionnaire. It was concluded that the assessment tool has the desired content validity. In this study, inferential and descriptive statistics have been used to analyze the information. For inferential analysis and to analyze the data, a one-sample t-test and an Independent two-sample t-test were used. Friedman tests were used for ranking. SPSS software version 23 was used to analyze the data.  Results: The findings of this study showed that the use of information and communication technologies gives rise to an increase in the access of tax authorities to tax information, increase in corporate tax compliance, reduction in tax compliance costs, increase in corporate income tax collection, rise of corporate income tax transparency, and higher effectiveness and efficiency of corporate income tax collection. And, statistically, there is a significant difference between the views of tax officials and senior managers and accountants of companies only in terms of the effect of using ICT on the amount of income tax collection, and in other cases, there is no significant difference.  Conclusion: The use of ICT affects the collection of income tax. Increasing investment in ICT is associated with increased tax collection.